HBeAg Is Indispensable for Inducing Liver Sinusoidal Endothelial Cell Activation by Hepatitis B Virus - Xie, Xiaohong; Luo, Jinzhuo; Zhu, Dan; Zhou, Wenqing; Yang, Xuecheng; Feng, Xuemei; Lu, Mengji; Zheng, Xin; Dittmer, Ulf; Yang, Dongliang; Liu, Jia (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aims: Liver sinusoidal endothelial cells (LSECs) serve as sentinel cells to detect microbial infection and actively contribute to regulating immune responses for surveillance against intrahepatic pathogens. We recently reported that hepatitis B e antigen (HBeAg) stimulation could induce LSEC maturation and abrogate LSEC-mediated T cell suppression in a TNF-α and IL27 dependent manner. However, it remains unclear how HBeAg deficiency during HBV infection influences LSEC immunoregulation function and intrahepatic HBV-specific CD8 T cell responses. Methods: The function of LSECs in regulating effector T cell response, intrahepatic HBV-specific CD8 T cell responses and HBV viremia were characterized in both HBeAg-deficient and -competent HBV hydrodynamic injection (HDI) mouse models. Results: LSECs isolated from HBeAg-deficient HBV HDI mice showed a reduced capacity to promote T cell immunity in vitro compared with those isolated from wild-type HBV HDI mice. HBeAg expression replenishment in HBeAg-deficient HBV HDI mice restored the HBV-induced LSEC maturation, and resulted in potent intrahepatic anti-HBV CD8 T cell responses and efficient control of HBV replication. Moreover, in vivo TNF-α, but not IL27 blockade in HBV HDI mice impaired HBV-specific CD8 T cell immunity and delayed HBV clearance. Conclusion: Our study underlines that HBeAg is indispensable for HBV-induced LSEC maturation to trigger intrahepatic HBV-specific T cell activation, and provides a new mechanism to elucidate the intrahepatic immune microenvironment regulation upon HBV exposure.